KONTRIBUSI MATA KULIAH PRASYARAT ANATOMI DASAR TERHADAP HASIL BELAJAR MATA KULIAH ANATOMI RADIOLOGI I MAHASISWA DIII AKADEMI TEKNIK RADIODIAGNOSTIK DAN RADIOTERAPI YAYASAN SINAR AMAL BHAKTI MEDAN T.A. 2017/2018 - DJAMIANDAR SIMAMORA; Endika Rosalinda Sirait (JURNAL PENELITIAN FISIKAWAN, 2019)
The purpose of this research is investigating whether are contributing the lecture preconditions of Basic Anatomy to the learning out comes Anatomy of radiology 1. The three Diploma of Akademi Teknic Radiodiagnostik dan Radioterapi Yayasan Sinar Amal Bhakti Medan. Populations of research are all of academic students who have followed the Basic Anatomy and Anatomy of Radiology I lecture, there are 40 academic student. As the research sample is totality of population. This research shown that contribution of precondition lecture Basic Anatomy to learning out comes Anatomy of Radiology I, where the Fregression are 1,08 < Ftable are 2,40 and rcorrelation are 0,82 > rtable are 0,31 on the significances degree 0,05 and index determinant (I) = 0,99.